Legal Aspects Of Electronic Signatures In E- Commerce Transactions - Enny Agustina; Muhamad Adystia Sunggara (Journal of World Conference (JWC), 2021)
Technological advances have brought about significant changes from the use of the Internet in human life. However, there are still many parties who do not understand how the position of electronic signatures that meet the requirements and standards, especially in financial technology transactions where the electronic signature function was essential. This study discusses the position of electronic signatures in financial technology transactions as well as legal remedies that can be taken if there was an electronic signature dispute. The type of research used in this paper was normative. The approach to the problem used in the writing of this research was the statute approach and the conceptual approach. The legal materials used in the writing of this study consist of primary legal materials, secondary legal materials, and tertiary legal materials. The analysis used in the writing of this research is descriptive qualitative. The conclusion in this study is that in accordance with applicable laws and regulations, electronic signatures must meet aspects ofs authenticity, integrity, and non-repudiation. With regard to fraud that causes losses to users of financial technology transactions, financial technology operators are liable for an error with a reversal of the burden of proof. Legal recognition in applicable laws and regulations confirms that electronic signatures can be used as evidence in court examinations. Legal remedies that can be taken if there is a dispute are through Litigation or Non-Litigation. The majority of business players prefer Non-Litigation legal remedies, namely alternative dispute resolution to resolve any problems that arise in business activities because the settlement system is more effective, fair, does not take up time, and is relatively cheaper.